2016
DOI: 10.1021/acsami.5b12524
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Low Adsorption Energy Ni–Mo Cluster Cocatalyst in Metal–Organic Frameworks for Visible Photocatalytic Hydrogen Evolution

Abstract: An effective cocatalyst is crucial for enhancing the visible photocatalytic performance of the hydrogen generation reaction. By using density-functional theory (DFT) and frontier molecular orbital (FMO) theory calculation analysis, the hydrogen adsorption free energy (ΔGH) of Ni-Mo alloy (458 kJ·mol(-1)) is found to be lower than that of Ni itself (537 kJ·mol(-1)). Inspired by these results, the novel, highly efficient cocatalyst NiMo@MIL-101 for photocatalysis of the hydrogen evolution reaction (HER) was fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(49 citation statements)
references
References 72 publications
2
46
0
1
Order By: Relevance
“…Besides other UiO-66/UiO-66-NH 2 [55,[145][146][147][148][149][150] and MIL-101/ MIL-101-NH 2 [151,152] associated work, the photocatalytic performances of MOF-supported catalysts, including UiO-type MOFs, [153][154][155] MOF-5, [56] MIL-125-NH 2 , [156,157] MIL-53-NH 2 , [158] Zr-porphyrin-based MOF (ZrPF), [159] and NU-1000 [160] are also summarized in Table 3. Besides other UiO-66/UiO-66-NH 2 [55,[145][146][147][148][149][150] and MIL-101/ MIL-101-NH 2 [151,152] associated work, the photocatalytic performances of MOF-supported catalysts, including UiO-type MOFs, [153][154][155] MOF-5, [56] MIL-125-NH 2 , [156,157] MIL-53-NH 2 , [158] Zr-porphyrin-based MOF (ZrPF), [159] and NU-1000 [160] are also summarized in Table 3.…”
Section: Mofs As Supportsmentioning
confidence: 99%
“…Besides other UiO-66/UiO-66-NH 2 [55,[145][146][147][148][149][150] and MIL-101/ MIL-101-NH 2 [151,152] associated work, the photocatalytic performances of MOF-supported catalysts, including UiO-type MOFs, [153][154][155] MOF-5, [56] MIL-125-NH 2 , [156,157] MIL-53-NH 2 , [158] Zr-porphyrin-based MOF (ZrPF), [159] and NU-1000 [160] are also summarized in Table 3. Besides other UiO-66/UiO-66-NH 2 [55,[145][146][147][148][149][150] and MIL-101/ MIL-101-NH 2 [151,152] associated work, the photocatalytic performances of MOF-supported catalysts, including UiO-type MOFs, [153][154][155] MOF-5, [56] MIL-125-NH 2 , [156,157] MIL-53-NH 2 , [158] Zr-porphyrin-based MOF (ZrPF), [159] and NU-1000 [160] are also summarized in Table 3.…”
Section: Mofs As Supportsmentioning
confidence: 99%
“…Zhen et al. reported that the noble metal‐free Ni–Mo@MIL‐101 catalyst sensitized with Eosin Y catalyzed the HER very close to natural photosynthesis . They showed that the hydrogen adsorption Gibbs energy (Δ G H ) of Ni 4 Mo NCs (458 kJ mol −1 ) is lower than that of the Ni−H ads (537 kJ mol −1 ) monometallic catalyst.…”
Section: Application Of Mncs In Energy Conversionmentioning
confidence: 99%
“…As already demonstrated, the nature of MNCs can be precisely controlled, which makes them promisingm odel materials to investigate the catalytic potentialo fn anoscale materials, thus providing ar oadmap for the successful synthesis of targeted nanocatalysts.Z hen et al reported that the noble metalfree Ni-Mo@MIL-101 catalyst sensitized with Eosin Yc atalyzed the HER very close to natural photosynthesis. [197] They showed that the hydrogen adsorption Gibbs energy (DG H )o fN i 4 Mo NCs (458 kJ mol À1 )i sl ower than that of the NiÀH ads (537 kJ mol À1 )m onometallic catalyst. On the basis of this concept they mechanistically showed that catalystf ollowst he Volmer reaction or initial discharge of H 2 Of ollowed by Heyrovsky and Tafel reaction as shown in Equations (5)- (7).…”
Section: Photo-electrochemical Water Splitting By Mncsmentioning
confidence: 99%
“…The MOF‐supported ultrafine AuNi alloy NPs showed significant activity for the catalytic hydrolysis of ammonia borane to generate hydrogen. Using the DSM method, Lu and coworkers reported the synthesis of bimetallic Ni–Mo alloy nanoclusters ( Figure ) inside the MIL‐101 matrix . NiMo@MIL‐101 exhibited good stability, high apparent quantum efficiency, and an excellent photocatalytic performance in comparison to the corresponding one‐component composites Ni@MIL‐101 and Mo@MIL‐101.…”
Section: Synthesis Strategies For Integration Of Active Mnps Into Mofsmentioning
confidence: 99%
“…Synthetic procedure of NiMo@MIL‐101 via the DSM method. Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Synthesis Strategies For Integration Of Active Mnps Into Mofsmentioning
confidence: 99%